Distinct neuropsychological profiles correspond to distribution of cortical thinning in inherited prion disease caused by insertional mutation. Issue 1 (17th August 2011) - Alner, K; Hyare, H; Mead, S; Rudge, P; Wroe, S; Rohrer, J D; Ridgway, G R; Ourselin, S; Clarkson, M; Hunt, H; Fox, N C; Webb, T; et al.
Abstract : Background: The human prion diseases are a group of universally fatal neurodegenerative disorders associated with the auto-catalytic misfolding of the normal cell surface prion protein (PrP). Mutations causative of inherited human prion disease (IPD) include an insertion of six additional octapeptide repeats (6-OPRI) and a missense mutation (P102L) with large families segregating for each mutation residing in southern England. Here we report for the first time the neuropsychological and clinical assessments in these two groups. Method: The cognitive profiles addressing all major domains were obtained for 26 patients (18 6-OPRI, 8 P102L) and the cortical thickness determined using 1.5T MRI in a subset of 10 (six 6-OPRI, four P102L). Results: The cognitive profiles were different in patients with the two mutations in the symptomatic phase of the disease. The 6-OPRI group had lower premorbid optimal levels of functioning (assessed on the NART) than the P102L group. In the symptomatic phase of the disease the 6-OPRI patients had significantly more executive dysfunction than the P102L group and were more impaired on tests of perception and nominal functions. There was anecdotal evidence of low premorbid social performance in the 6-OPRI but not P102L patients. Cortical thinning distribution correlated with the neuropsychological profile in the 6-OPRI group principally involving the parietal, occipital and posterior frontal regions. The small number of patients in the P102L group precluded statistical comparison between the groups. Conclusions: The 6-OPRI patients had more widespread and severe cognitive dysfunction than the P102L group and this correlated with cortical thinning distribution.